2017
DOI: 10.1103/physrevc.95.044313
|View full text |Cite
|
Sign up to set email alerts
|

Electron spectra in forbiddenβdecays and the quenching of the weak axial-vector coupling constantgA

Abstract: Electron spectra in forbidden β decays and the quenching of the weak axial-vector coupling constant gA Kostensalo, Joel; Haaranen, Mikko; Suhonen, Jouni Kostensalo, J., Haaranen, M., & Suhonen, J. (2017). Electron spectra in forbidden β decays and the quenching of the weak axial-vector coupling constant gA. Physical Review C, 95 (4) Evolution of the electron spectra with the effective value of the weak axial-vector coupling constant g A was followed for 26 first-, second-, third-, fourth-and fifth-forbidden β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(99 citation statements)
references
References 36 publications
(83 reference statements)
3
95
1
Order By: Relevance
“…The only exception is the undetected fourth-forbidden β − decay branch of 50 V, for which the branching ratio has been predicted to be ≈2% by a recent shell-model calculation [36]. An earlier study [30] of the g A -driven evolution of the electron spectra of odd-A nuclei demonstrated that the second and especially the fourth-forbidden nonunique β-decay spectra depend strongly on the effective value of the weak axial-vector coupling constant. [36,45,46], so the study of these decays is somewhat challenging experimentally.…”
Section: A Electron Spectra and The Effective Value Of G Amentioning
confidence: 97%
See 4 more Smart Citations
“…The only exception is the undetected fourth-forbidden β − decay branch of 50 V, for which the branching ratio has been predicted to be ≈2% by a recent shell-model calculation [36]. An earlier study [30] of the g A -driven evolution of the electron spectra of odd-A nuclei demonstrated that the second and especially the fourth-forbidden nonunique β-decay spectra depend strongly on the effective value of the weak axial-vector coupling constant. [36,45,46], so the study of these decays is somewhat challenging experimentally.…”
Section: A Electron Spectra and The Effective Value Of G Amentioning
confidence: 97%
“…[32,33]. As in the previous SSM studies [20,21,30] we go beyond the earlier studies [32,33] and take into account the next-to-leading-order terms of the shape function. The details of the next-to-leading order shape factors are discussed in [21].…”
Section: Theoretical Formalismmentioning
confidence: 99%
See 3 more Smart Citations